Differences of airborne and mural microorganisms in a 1,500-year-old Xu Xianxiu’s Tomb, Taiyuan, China - Liu, Jiangyun; Wu, Fasi; Xiang, Ting; Ma, Wenxia; He, Dongpeng; Zhang, Qi; Wang, Wanfu; Duan, Yulong; Tian, Tian; Feng, Huyuan (Frontiers in Microbiology, 2023)
Background Microbial colonization represents one of the main threats to the conservation of subterranean cultural heritage sites. Recently, the microbial colonization on murals in tombs has gradually attracted attention. Methods In this study, a total of 33 samples, including 27 aerosol samples and 6 mural painting samples, were collected from different sites of Xu Xianxiu’s Tomb and analyzed using culture-dependent methods. We compared the diversities of culturable bacteria and fungi isolated from the air and murals and explored the potential impacts of microorganisms on the biodeterioration of the murals. Results Phylogenetic analyses revealed that the culturable bacteria belonged to Bacillus, Microbacterium, Lysobacter and Arthrobacter. And the most of fungal belonged to the Penicillium, Cladosporium and Aspergillus genera. The composition and structure of airborne bacteria and fungi outside the tomb were both significantly different from that inside the tomb. The variation trends of airborne bacterial and fungal concentrations at different sampling sites were remarkably similar. Bacillus frigoritolerans, Bacillus halotolerans, Bacillus safensis, Exiguobacterium mexicanum, Microbacterium trichothecenolyticum, and Micrococcus yunnanensis were bacterial species commonly isolated from both the mural and air environments. Fungal species commonly isolated from aerosol samples and mural painting samples were Alternaria alternata, Cladosporium cladosporioides, Penicillium brevicompactum, and Peyronellaea glomerata. The prediction of the ecological functions of the bacteria revealed that chemoheterotrophy or aerobic_chemoheterotrophy accounted for substantial relative proportions in all sample types. Conclusion These results suggest that the aerosol circulation between the inside and outside environments of the tomb was weak and that the outside environment had yet to have an impact on the air microbial community inside the tomb. Selective colonization of microorganisms, which is mediated by interaction between microorganisms and special microenvironmental factors, is an important reason for the biodeterioration of murals.